2020
DOI: 10.1101/2020.07.13.20151977
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

MIND diet associated with later onset of Parkinson’s disease

Abstract: Background: The MIND diet has been linked with prevention of cognitive decline but has not been fully assessed in the context of Parkinson's disease (PD). Objective: To determine whether MIND diet adherence is associated with the age of Parkinson's disease onset. Methods: Food Frequency Questionnaires from 181 participants with PD were scored for MIND adherence and correlated with age of onset using univariate and multivariate linear models. Results: MIND adherence scores positively correlated with age of onse… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
(38 reference statements)
0
3
0
Order By: Relevance
“…Since adhering to GFD is a tough ally [ 54 , 119 ], several alternative ways to decrease gluten-brain exposure might be envisioned. GF-Mediterranean diet [ 120 ], might be very rewarding as Mediterranean diet adherence significantly correlated with 8.4 years of later onset of PD [ 121 ]. The dysbiosis in CD and the gluten degrading microbial enzyme (glutenase) capacity might suggest probiotic and lactobacilli enhancing prebiotic therapies [ 122 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since adhering to GFD is a tough ally [ 54 , 119 ], several alternative ways to decrease gluten-brain exposure might be envisioned. GF-Mediterranean diet [ 120 ], might be very rewarding as Mediterranean diet adherence significantly correlated with 8.4 years of later onset of PD [ 121 ]. The dysbiosis in CD and the gluten degrading microbial enzyme (glutenase) capacity might suggest probiotic and lactobacilli enhancing prebiotic therapies [ 122 ].…”
Section: Discussionmentioning
confidence: 99%
“…120 A recent cross-sectional study showed a correlation between adherences with the MIND or Mediterranean-style diet with later age of PD onset in a Canadian PD cohort—prospective studies are needed to further investigate a possible influence of this diet on PD risk. 121…”
Section: Diet and Nutritionmentioning
confidence: 99%
“…5,6 In this regard, the Mediterranean diet (MD) has been proposed as a healthy dietary pattern with increasing evidence supporting its beneficial effects towards age-related pathologies, including neurodegenerative disorders and cognitive dysfunctions like AD and PD. [7][8][9] This potential of MD has been mainly related to its high content in plant foods such as fruits, vegetables, and olive oil, which are sources of an array of bioactive compounds. [10][11][12] Hydroxytyrosol (HT) and tyrosol (TYRS) are the major phenolic compounds present in virgin olive oil (VOO) (0.39-41 mg kg −1 and 0.2-32.9 mg kg −1 , respectively), and table olives (14.5-3833 mg kg −1 and 0.435-353.5 mg kg −1 , respectively).…”
Section: Introductionmentioning
confidence: 99%